β-sheets in serum protein are independent risk factors for coronary lesions besides LDL-C in coronary heart disease patients - Li, Yu-lin; Xie, Jia-ying; Lu, Bin; Sun, Xiao-di; Chen, Fang-fang; Tong, Zhou-jie; Sai, Wen-wen; Zhang, Wei; Wang, Zhi-hao; Zhong, Ming (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary heart disease (CHD) patients with standard low-density lipoprotein cholesterol (LDL-C) remain at risk of cardiovascular events, making it critical to explore new targets to reduce the residual risk. The relationship between β-sheet conformation and CHD is gaining attention. This study was designed to compare the coronary lesions in CHD patients with varying LDL-C and evaluate whether serum β-sheets are associated with coronary damage. Methods Two hundred and one patients diagnosed with stable CHD were recruited and divided into four groups according to LDL-C. Baseline information, coronary lesion-related indicators, and peripheral blood samples were collected. Serum β-sheet content was determined by thioflavin T fluorescence. Results The baseline information was comparable in CHD patients with different LDL-C. No difference was found in indicators relevant to coronary lesions among groups. The content of β-sheet was negatively correlated with LDL-C. Multiple linear regression revealed that serum β-sheet was positively correlated with coronary lesion when risk factors such as age, smoking, and LDL-C were controlled. Conclusions This is the first study that reports the serum β-sheet levels of CHD patients being gradually increased with decreasing LDL-C when coronary lesions were comparable. Serum β-sheet might exacerbate the coronary lesions in CHD patients independent of known risk factors such as LDL-C.